2021
DOI: 10.13057/biodiv/d220247
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and cytotoxic evaluation of Bauhinia scandens leaf extracts using HeLa and T47D cell lines

Abstract: Abstract. Lianah L, Khasanah RAN, Pranatami DA, Krisantini K. 2021. Phytochemical screening and cytotoxic evaluation of Bauhinia scandens leaf extracts using HeLa and T47D cell lines. Biodiversitas 22: 913-919. The aim of the study was to analyze the phytochemical contents and todetermine the cytotoxic activities of Bauhinia scandens leaf ethanol extracts against HeLa (human cervical cancer) and T47D (breast cancer) cell culture lines. Using a standard protocol, it was found that leaf extract of B. scandens co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Bauhinia scandens L. belonging to the Leguminosae family is known as 'chain tree' and distinctively dispersed in Indonesia including Semarang, Central Java. Its morphologic characteristics have been described previously in our publication (Lianah, 2016;Lianah et al, 2021). In summary, Bauhinia scandens is liana with ornamental value; the stem forms into a 'monkey ladder' when older; the fruits are pea shaped with 1 to 2 seeds.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Bauhinia scandens L. belonging to the Leguminosae family is known as 'chain tree' and distinctively dispersed in Indonesia including Semarang, Central Java. Its morphologic characteristics have been described previously in our publication (Lianah, 2016;Lianah et al, 2021). In summary, Bauhinia scandens is liana with ornamental value; the stem forms into a 'monkey ladder' when older; the fruits are pea shaped with 1 to 2 seeds.…”
Section: Introductionsupporting
confidence: 53%
“…exhibited antioxidant activities (Amarowicz, 2007;Brunetti et al, 2013;Graßmann, 2005;Pietta, 2000). The previous studies, Lianah et al (2021) have reported the presence of phytochemicals with high concentration in the ethanolic extracts of Bauhinia scandens leaves, namely total phenols (17.57±0.098% w/w) and saponins (19.42±0.091% w/w), followed by tannins (1.24±0.035% w/w), alkaloids (1.31±0.001% w/w), and steroids (0.08±0.007% w/w). Nevertheless, a screening of phytochemicals in Bauhinia scandens bark has not yet been done.…”
Section: Fig 2 Linear Regression Analysis For % Inhibition Of Ethanol...mentioning
confidence: 93%
See 1 more Smart Citation
“…Indian tribal and non-tribal people of different regions use the plant pod and seeds as tonic and to overcome the problem of libido. [6] DISCUSSION: Medicinal plants play an important role in human health and have potential to treat various diseases 32 . Available scientific research on B. purpurea L. is suggested a huge biological potential of this plant leaf, flower and bark but there is very limited data available on pod (fruit) 5 .…”
Section: Flowermentioning
confidence: 99%
“…The chloroform layer formed was put into a 10 mL test tube, and chloroform to 10 mL was added. The resulting solution was tested using a spectrophotometer with a wavelength of 430 nm [22]. Determination of total flavonoids.…”
Section: Phytochemical Analysismentioning
confidence: 99%